The role of immunotherapy sensitizers and novel immunotherapy modalities in the treatment of cancer - Guilherme Sacchi de Camargo Correia; Yujie Zhao; Rami Manochakian; Yanyan Lou (Frontiers in Oncology, 2024)
The importance of the immune system in the response against cancer has always been a subject of intense investigation. The advent of immune checkpoint inhibitors has transformed the landscape of oncologic treatments, while expanding the understanding of this disease’s pathophysiology. Consequently, many therapies are being investigated, with interventions directed at different steps and pathways of the immune response. Relevantly, immunotherapy sensitizers have arisen as approaches focused on the synergistic effects of immunotherapy combination, or the combination of immunotherapy and other treatment modalities, such as chemotherapy or radiation therapy. Concomitantly, novel immunotherapy modalities are also in development. Approaches focusing from the tumor intrinsic pathways to the tumor microenvironment and ex-vivo interventions, such as CAR-T cell therapies and tumor-infiltrating lymphocytes are important examples. Although many of those interventions were initially envisioned as standalone options, their combination has demonstrated promising results in early-phase in vitro studies and clinical trials. The possibility of coupling different immunotherapy modalities, as well as with other techniques, further strengthen the concept of sensitizers, allowing for deeper and more robust responses in cancer treatment. This review aims to present an overview of the concepts of these sensitizing mechanisms that are the basis for the synergistic effects of immunotherapy combination, or the combination of immunotherapy and a multitude of therapeutic strategies. Novel immunotherapy modalities are also presented, focusing on the potential of combining them with sensitizer interventions. Understanding the complexity underlying these principles may be the key for future breakthroughs and improved patient outcomes.